Complementary and alternative medicine use by glioma patients in Switzerland. Issue 3 (12th October 2018) - Eisele, Günter; Roelcke, Ulrich; Conen, Katrin; Huber, Fabienne; Weiss, Tobias; Hofer, Silvia; Heese, Oliver; Westphal, Manfred; Hertler, Caroline; Roth, Patrick; Weller, Michael
Abstract: Background: During the course of disease, most glioma patients learn that there is no cure for their tumor. It is therefore not uncommon for patients or caregivers to seek complementary and alternative medicine (CAM) treatments. Patterns of CAM use vary across the globe, but little is known about the type of, and motivation for, CAM use in most countries. Methods: Here we conducted a cross-sectional survey of CAM use in patients harboring gliomas of World Health Organization (WHO) grades II to IV at 3 specialized neuro-oncology centers in Switzerland. Results: Of 208 patients who returned the survey, approximately half reported having used or using CAM. CAM use was associated with younger age. Patients suffering from WHO grade II gliomas were less likely to indicate CAM use. The leading motivation for CAM use was to contribute actively to the treatment of the disease. CAM use was commonly not counseled or supervised by a health care professional. Cost and issues of reimbursement were not an important factor in the decision against or for CAM use. Conclusions: Physicians caring for glioma patients should be aware of and explore CAM use to better understand patients' attitudes toward their disease, to provide counseling, and to identify potential interactions of CAM with standard treatments for gliomas.